2016
DOI: 10.1542/peds.2015-2851j
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Treatment of Anxiety in Youth With Autism Spectrum Disorders

Abstract: OBJECTIVES: Anxiety is one of the most prevalent co-occurring symptoms in youth with autism spectrum disorder (ASD). The assessment and treatment recommendations proposed here are intended to help primary care providers with the assessment and treatment of anxiety in ASD. METHODS: The Autism Speaks Autism Treatment Network/Autism Intervention Research on Physical Health Anxiety Workgroup, a multidisciplinary team of clinician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 43 publications
4
56
0
1
Order By: Relevance
“…Following further replication, the SCAS‐P appears to be a reasonably good choice as a freely available first line screening tool for typical DSM‐derived anxiety in ASD, provided that it is employed alongside other multi‐informant and multi‐method information gathering approaches (i.e., using the ASC‐ASD by Rodgers et al, to also examine more ASD‐related anxiety difficulties; or the ADIS C/P ASD addendum clinical interview by Kerns and colleagues, 2014; see also Vasa et al, ). If the original SCAS‐P is used, we recommend the use of the total score as a general screen for anxiety, and not of the separate subscales, as the underlying subscale/factor structure remains inconsistent and unclear and requires further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Following further replication, the SCAS‐P appears to be a reasonably good choice as a freely available first line screening tool for typical DSM‐derived anxiety in ASD, provided that it is employed alongside other multi‐informant and multi‐method information gathering approaches (i.e., using the ASC‐ASD by Rodgers et al, to also examine more ASD‐related anxiety difficulties; or the ADIS C/P ASD addendum clinical interview by Kerns and colleagues, 2014; see also Vasa et al, ). If the original SCAS‐P is used, we recommend the use of the total score as a general screen for anxiety, and not of the separate subscales, as the underlying subscale/factor structure remains inconsistent and unclear and requires further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…458,459 Anxiety disorders are most commonly identified in children with ASD and typical cognitive and language abilities. 468,469 Symptoms may be present in early childhood and manifest as behavioral challenges, such as overreactivity. Biological predisposition to both ASD and anxiety may be attributable to common genetic factors and/or altered neurophysiologic responses to stress.…”
Section: Adhdmentioning
confidence: 99%
“…• Behavioral rigidity, insistence on sameness Anticonvulsants (valproic acid and divalproex sodium) 613,621,622 Modest improvement has been reported with divalproex sodium treatment May have improvement with topiramate as a second agent with risperidone Most antiseizure drugs have potential for sedation, cognitive adverse events SSRI (fluoxetine, fluvoxamine) 480,509,611,612,[623][624][625][626][627] Studies to date have not revealed effectiveness of SSRI medications for repetitive behaviors related to ASD, although they may diminish anxiety SSRIs may be effective for reducing symptoms of OCD and of anxiety when included in a comprehensive approach to treatment Need comprehensive behavioral approaches to minimize repetitive behaviors Anxiety, depression SSRIs 469,628 Anxiety relief has been reported in trials of citalopram and buspirone, with fluvoxamine revealing some effect in female patients with ASD; documented utility in children and youth without ASD a-adrenergic (clonidine, guanfacine)…”
Section: • Compulsionsmentioning
confidence: 99%
See 2 more Smart Citations